Ten Spooky Pumpkins - Grimly, Gris (New York : Orchard Books, an imprint of Scholastic Inc., 2021)
10 little pumpkins, sitting in a line, looking for a cat and they found nine. The wind said SWOOSH and the gate went CREAK. The owl cried WHOOOO, we all screamed EEK! Celebrated creator Gris Grimly, widely known for his gothic style illustrations, puts a spooky twist on a favorite preschool rhyme in this Halloween read-aloud.
Keywords: Halloween -- Juvenile fiction; Counting -- Juvenile fiction; Halloween -- Fiction; Counting -- Fiction; Stories in rhyme; Picture books; Counting books